Konten TikTok Kesehatan Mental dan Dampaknya Terhadap Pengetahuan Mengenai Toxic Relationship - Helsa, Helsa; Astuti, Prida Ariani Ambar (Research and Community Service UNIVERSITAS KALBIS, 2024)
Mental health is often disregarded because it does not involve physical pain. However, it is just as important as physical health, and many Indonesians still need to understand it fully. To address this issue, a research study was conducted to examine how mental health content on TikTok affects Generation Z's understanding of toxic relationships. The study analyzed the TikTok account @sundarindah, which posted content about toxic relationships between January and November 2023 and used Uses and Gratification theory to analyze research findings. The study used an explanatory survey with a quantitative approach and a positivistic paradigm. The findings indicate that there is a positive correlation between mental health content and knowledge about toxic relationships. However, the study also found that the impact of TikTok content on mental health was moderate. The findings of this study are understandable because the mass audience can no longer be seen as passive recipients of any message conveyed through the media. Audiences now actively choose media that can fulfill their needs and desires. However, TikTok has become an attractive medium for Generation Z because of its audio-visual advantages. The information conveyed through this account is casual and has entertainment elements.